Interrogations And The Right To Remain Silent - A Comparative Approach - Bilalli Arta (SEEU Review, 2015)
Interrogations are a very specific component of any criminal investigation. The answers gained through interrogative process provides information that are considered as direct evidences. In contemporary criminal procedure, the court is not absolved from gaining other evidences, even in cases when the defendant confesses his/her guiltiness. This is a mechanism for excluding the inquisitorial approach for extracting compulsory confessions. The modern procedure uses a variety of mechanisms to guarantee that the defendant will not be compelled to confess guilt.